Pengaruh Persepsi Siswa Tentang Tata Ruang Dan Persepsi Siswa Tentang Kualitas Pelayanan Terhadap Minat Berkunjung Ke Perpustakaan - Novia Srizalni; Agus Irianto (Universitas Negeri Padang, 2023)
This study aims to describe: 1) the effect of students' perceptions of spatial planning on interest in visiting the library at SMKN business and management groups in Padang, 2) the effect of students' perceptions of service quality on interest in visiting the library at SMKN business and management groups in Padang, 3) the effect of students' perceptions of spatial planning and service quality on interest in visiting the library at SMKN business and management Padang. This type of research is descriptive and associative research. The population in this study were all students of SMKN business and management groups in Padang City with a total sample of 96 people who were taken using proportional random sampling technique. The type of data in this study is primary data. Data collection techniques using questionnaires. The data analysis technique used is multiple regression analysis. The results showed that students' perceptions of spatial planning and students' perceptions of service quality had a positive and significant effect on students' interest in visiting the library at SMKN business and management groups in Padang City.